Neuroprotective Role of Akt in Hypoxia Adaptation in Andeans - Zhao, Helen; Lin, Jonathan; Sieck, Gary; Haddad, Gabriel G. (Frontiers in Neuroscience, 2021)
Chronic mountain sickness (CMS) is a disease that potentially threatens a large segment of high-altitude populations during extended living at altitudes above 2500m. Patients with CMS suffer from severe hypoxemia, excessive erythrocytosis and neurologic deficits. The cellular mechanisms underlying CMS neuropathology remain unknown. We previously showed that iPSC-derived CMS neurons have altered mitochondrial dynamics and increased susceptibility to hypoxia-induced cell death. Genome analysis from the same population identified many ER stress-related genes that play an important role in hypoxia adaptation or lack thereof. In the current study, we showed that iPSC-derived CMS neurons have increased expression of ER stress markers Grp78 and XBP1s under normoxia and hyperphosphorylation of PERK under hypoxia, alleviating ER stress does not rescue the hypoxia-induced CMS neuronal cell death. Akt is a cytosolic regulator of ER stress with PERK as a direct target of Akt. CMS neurons exhibited lack of Akt activation and lack of increased Parkin expression as compared to non-CMS neurons under hypoxia. By enhancing Akt activation and Parkin overexpression, hypoxia-induced CMS neuronal cell death was reduced. Taken together, we propose that increased Akt activation protects non-CMS from hypoxia-induced cell death. In contrast, impaired adaptive mechanisms including failure to activate Akt and increase Parkin expression render CMS neurons more susceptible to hypoxia-induced cell death.